Assessing Precision in All-Ceramic Fixed Restorations: Unveiling the Marginal Fit Through Digital and Traditional Impressions—A Comprehensive Systematic Review and Meta-Analysis - Alqahtani, Waleed M. S.; Yousief, Salah A.; Demachkia, Amir Mohidin R.; Demachkia, Mohidin R.; Barakat, Ali; Dimashkieh, Mohiddin R.; Mekkey, Mahmoud Abdallah M.; Abdelglel, Ahmed Mohammed Sleem; Waly, Ahmed S.; Bamanie, Rawana Mohammed Saieed; Alnafisah, Dalal Abdulaziz (European Journal of Dentistry, 2025)
The marginal fit of all-ceramic fixed restorations is critical to long-term success. This comprehensive study and meta-analysis assessed the marginal fit of restorations manufactured using digital versus conventional impression procedures. We conducted a comprehensive search of electronic databases such as PubMed, Cochrane CENTRAL, Web of Science, and Scopus for publications published up to 2023. Eligible papers comparing the marginal fit of all-ceramic permanent restorations made using digital and conventional impressions were considered. A total of 19 studies met the inclusion criteria. The pooled analysis revealed that restorations fabricated from digital impressions exhibited a significantly better marginal fit than those from conventional impressions and showed a mean marginal gap of –13.76 µm (95% confidence interval: [–24.77, –2.76], p-value = 0.01). Subgroup analysis by type of digital impression system demonstrated consistent superiority of zironica material over other ones. However, high heterogeneity was observed among the included studies (I2 = 90.74%). Digital impression restorations show superior marginal fit compared with conventional impressions, but high heterogeneity requires cautious interpretation and further well-designed studies to validate results.
Keywords: marginal fit; restoration; ceramic; digital